Sakarifikasi daun nanas (Ananas comosus) dengan lignoselulase dari bakteri endosimbion insang temilok (Bactronophorus thoracites) - Khoirul Muslih; Denny Syaputra (Journal of Aquatropica Asia, 2015)
Wood borer shellfish temilok (Bactronophorus thoracites) is a species of clams from family Teredinidae which used the wood as the main source of their food. The gill of temilok is inhabited by bacterias whom able to use the cellulose rich-fiber of the wood. The finding of bacterias which able to produce a cellulose-degrading enzymes was very usefull to improve the saccharification efficiency and effectivity of cellulose-rich material that comes from crops or papers from offices disposal. The aim of the research was to isolate the bacteria from the gill of temilok, and to know the saccharification kinetics of fiber of pineapple leafs by the secreted cellulase from the bacteria in the form of soluted glucose. Isolated bacterias was growth in a sterilized sea water (salinity of 20o/oo) at 16-20 oC without the addition of nitrogen sources to get the direct atmospheric dinitrogen-using bacteria. The interaction effects of incubation periods (24, 48, and 72 hours), and substrate concentrations (0,2%, 0,4%, and 0,6%) were investigated by measuring and calculating the concentrations of soluted glucose in the media using phenol-sulfate (phesul) method. Experimental design using factorial completed split plot, and data processing using Microsoft Excell. Variance analyses of soluted glucose concentrations showed that the interactions give no significant effects on soluted glucose consentrations in the media. The highest concentration was 88,1722 ppm (incubation period 72 h, substrate concentration 0,2%), and the lowest was 28,8340 ppm (incubation period 48 h, substrate concentration 0,2%).